Rasulullah’s Sufism: The Principle of Balance of Islamic Esotericism And Exotericism - Syaik Abdillah; Ris'an Rusli; Hossein Muttaqi; Moh In’ami (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Sufism is a deeply personal spiritual experience that cannot be fully explained through scientific methods. Rooted in the Qur’an and Sunnah, it emphasizes doctrines such as piety, sincerity, patience, and purification of the soul. However, the historical development of Sufism has involved external influences, sometimes resulting in internal controversies. These have led to criticisms and accusations of heresy, particularly from literalist groups such as ahl aldhawahir, especially concerning doctrines like wahdat al-wujud. Despite this, Sufism remains strongly grounded in the prophetic tradition. This study aims to explore the characteristics of Sufism practiced by the Prophet Muhammad and how it differs from or aligns with the categories of Sufism developed later in Islamic history. The research uses a qualitative method with an anthropological approach, seeking to uncover the meanings behind spiritual practices and symbols through field-based interpretation. Data were collected through literature analysis and interpreted to reveal underlying theological and spiritual meanings. The findings demonstrate that the Prophet's model of Sufism embodies a balanced form of spirituality, integrating both exoteric (shari‘ah) and esoteric (haqiqah) dimensions within the framework of Islamic monotheism. This research contributes to the field of Islamic spirituality by offering a novel perspective on Sufism as lived and exemplified by the Prophet, a form of balance not extensively explored in previous studies. It affirms that the essence of Sufism lies in harmonizing outward religious practices with inner spiritual realization, thereby enriching the discourse on the legitimacy and origins of Islamic mysticism.